MPV17 mutations in juvenile‐ and adult‐onset axonal sensorimotor polyneuropathy. Issue 1 (25th October 2018) - Baumann, Matthias; Schreiber, Herbert; Schlotter‐Weigel, Beate; Löscher, Wolfgang N.; Stucka, Rolf; Karall, Daniela; Strom, Tim M.; Bauer, Peter; Krabichler, Birgit; Fauth, Christine; Glaeser, Dieter; Senderek, Jan
Abstract : MPV17 encodes a putative channel‐forming protein of the inner mitochondrial membrane and is involved in mitochondrial deoxynucleotide homeostasis. MPV17 mutations were first reported in patients with Navajo neurohepatopathy, an autosomal recessive mitochondrial DNA depletion syndrome, characterized by early‐onset liver failure, failure to thrive as well as central and peripheral neurological involvement. Recently, two patients with juvenile‐onset peripheral sensorimotor neuropathy associated with an MVP17 c.122G>A (p.Arg41Gln) variant have been reported. Here, we describe five additional patients from two unrelated families with sensorimotor axonal neuropathy without hepatocerebral affection caused by homozygous MPV17 variants. Patients of the first family carried the known c.122G>A variant and affected individuals of the second family had a novel c.376‐9T>G near‐splice variant, which was shown to result in an in‐frame deletion of 11 amino acids. This report provides further evidence that MPV17 mutations should be considered in patients with pure, non‐syndromic axonal neuropathy. Abstract :